Absence of Fms-like tyrosine kinase 3 ligand (Flt3L) signalling protects against collagen-induced arthritis. - Ramos, M; Karpus, O; Broekstra, P; Aarrass, S; Jacobsen, SE; Tak, P; Lebre, M (2015)
OBJECTIVE: Comprehending the mechanisms that regulate activation of autoreactive T cells and B cell antibody production is fundamental for understanding the breakdown in self-tolerance and development of autoimmunity. Here we studied the role of Fms-like tyrosine kinase 3 ligand (Flt3L) signalling in the pathogenesis of collagen-induced arthritis (CIA). METHODS: CIA was induced in mice lacking Flt3L (Flt3L(-/-)) and wild-type (WT) littermates (C57/BL6, 8-10 weeks old). Mice were killed in the initial phase (acute phase: experiment 1) and late phase (chronic phase: experiment 2) of the disease. Arthritis severity was assessed using a semiquantitative scoring system (0-4), and histological analysis of cellular infiltration, cartilage destruction and peptidoglycan loss was performed. Phenotypic and functional analysis of T and B cells, FoxP3 expression, activation and lymphocyte costimulatory markers, and cytokine production were performed ex vivo by flow cytometry in lymph nodes. Serum collagen type II (CII)-specific antibodies were measured by ELISA. RESULTS: Flt3L(-/-) mice showed a marked decrease in clinical arthritis scores and incidence of arthritis in both acute and chronic phases of CIA compared with WT mice. Moreover, decreased synovial inflammation and joint destruction was observed. Both the magnitude and quality of T cell responses were altered in Flt3L(-/-). In the acute phase, the amount of CII-specific IgG2a antibodies was lower in Flt3L(-/-) than WT mice. CONCLUSIONS: These results strongly suggest a role for Flt3L signalling in the development of arthritis.